Potato (Solanum Tuberosum L.): A Staple Food for The Poor and A Culinary Delicacy for The Affluent—Socio-Economic Impact and Future Prospects (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Potato (Solanum tuberosum L.) is one of the most important food crops worldwide, playing a dual role as a staple food for economically weaker populations and as a culinary delicacy for affluent societies. It is valued for its high productivity, adaptability to diverse agro-climatic conditions, and rich nutritional profile comprising carbohydrates, dietary fibre, vitamins, minerals, and bioactive compounds. Potatoes contribute significantly to food security, poverty alleviation, rural employment, and agro-industrial development. Simultaneously, processed and gourmet potato-based products dominate global food markets and modern gastronomy. This review highlights the nutritional composition, socio-economic importance, culinary diversity, health implications, and future prospects of potato cultivation, emphasizing its role in sustainable food systems and socio-economic development.